New aspects in the management of pneumonia. Issue 1 (December 2016) - Prina, Elena; Ceccato, Adrian; Torres, Antoni
Abstract Despite improvements in the management of community-acquired pneumonia (CAP), morbidity and mortality are still high, especially in patients with more severe disease. Early and appropriate antibiotics remain the cornerstone in the treatment of CAP. However, two aspects seem to contribute to a worse outcome: an uncontrolled inflammatory reaction and an inadequate immune response. Adjuvant treatments, such as corticosteroids and intravenous immunoglobulins, have been proposed to counterbalance these effects. The use of corticosteroids in patients with severe CAP and a strong inflammatory reaction can reduce the time to clinical stability, the risk of treatment failure, and the risk of progression to acute respiratory distress syndrome. The administration of intravenous immunoglobulins seems to reinforce the immune response to the infection in particular in patients with inadequate levels of antibodies and when an enriched IgM preparation has been used; however, more studies are needed to determinate their impact on outcome and to define the population that will receive more benefit.